The Effect of Preoperative Symptom Duration on Postoperative Outcomes After a Tubular Lumbar Microdiscectomy. Issue 1 (February 2019) - Basques, Bryce A.; Haws, Brittany E.; Khechen, Benjamin; Louie, Philip K.; Patel, Dil V.; Bawa, Mundeep S.; Movassaghi, Kamran; Cardinal, Kaitlyn L.; Guntin, Jordan A.; Singh, Kern
Abstract : Study Design: This is a retrospective cohort study. Objective: This study aims to characterize the effect of preoperative symptom duration on postoperative outcomes after minimally invasive lumbar microdiscectomy (MIS LD). Summary of Background Data: It is unknown whether extended nonoperative treatment before MIS LD has implications for long-term clinical outcomes even after surgery is performed. Materials and Methods: A prospectively maintained surgical registry of patients undergoing MIS LD by a single surgeon between 2013 and 2017 was reviewed. Preoperative symptom duration was dichotomized into 2 groups (⩽6 and >6 mo). Only patients with full clinical data at 6 months postoperative follow-up were included in the study. Clinical outcomes were assessed at 6, 12 weeks, and 6 months after surgery. The number of patients obtaining a minimum clinically important difference was assessed. Groups were compared with the χ 2 analysis and the student t tests for categorical and continuous data, respectively. Results: In total, 94 patients were identified. A total of 45 patients (47.9%) had symptom duration ⩽6 months. No differences in baseline characteristics were found ( P >0.05). Patients with shorter symptom duration had significantly greater improvement in Oswestry Disability Index scores at 6 weeks ( P =0.004), 12 weeks ( P =0.022), and 6 months ( P =0.005). Patients with shorter duration of symptoms also obtained minimum clinically important difference for Oswestry Disability Index at a greater rate than those with longer duration of symptoms ( P =0.015). Conclusions: Although patients who underwent MIS LD within 6 months of symptom onset had similar baseline characteristics compared with patients who underwent surgery after 6 months of symptoms, the patients with longer preoperative symptom duration had worse functional outcomes at 6 months after surgery. These results suggest that earlier MIS lumbar microdiscectomy may provide a functional benefit for patients. Further studies should therefore evaluate the efficacy of nonoperative treatment in the setting of lumbar herniated nucleus pulposus, as prolonged conservative management may potentially impair functional recovery after surgery.